2013
DOI: 10.1007/s13277-013-0839-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life estimate in stomach, colon, and rectal cancer patients in a hospital in China

Abstract: The objective of this study was to investigate the outcome and coping patterns of patients with stomach, colon, and rectal cancer in a hospital in China. Health-related quality of life was assessed in 118 stomach, colon, and rectal cancer patients in Chinese People's Liberation Army General Hospital, Beijing, China, using the generic version of the European Organization for Research and Treatment of Cancer Quality of Life (QOL) Questionnaire Core 30 Items, Self-rated Anxiety Scores (SAS), Self-rated Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Such findings may be related to the symptoms associated with GIT cancers, being mostly affecting the usual pattern of eating, besides the embarrassing conditions related to the surgical intervention of bowel that may be maximized by radiotherapy or chemotherapy. Similar findings were reported by studies in China (Deng, Lan, & Luo, 2013) and Turkey (Alacacioglu et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Such findings may be related to the symptoms associated with GIT cancers, being mostly affecting the usual pattern of eating, besides the embarrassing conditions related to the surgical intervention of bowel that may be maximized by radiotherapy or chemotherapy. Similar findings were reported by studies in China (Deng, Lan, & Luo, 2013) and Turkey (Alacacioglu et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…In a healthrelated QOL in 118 stomach, colon, and rectal cancer patients in Chinese People's Liberation Army General Hospital, Beijing, China, using various scores including SDS and Social Support Requirement Scale (SSRS) found anxiety and depression were associated with cancer diagnosis, treatment, and gender. 18 Younger age is more liable to depression, as our result suggests ( Table 3). The work, social life and active interpersonal relation of young age patient may be adversely affected by stoma and more prone to depression.…”
Section: Resultssupporting
confidence: 62%
“…Correlation analysis demonstrated that comfort level was positively related to the confronting coping mode and negatively correlated to the avoidance and acceptance-resignation coping mode. Consistent with a previous study [18], only the acceptance-resignation coping mode was entered into the regression equation, and it was an important negative factor influencing the level of comfort. Resignation coping can negatively impact quality of life and physical and psychological comfort.…”
Section: 2mentioning
confidence: 70%